PECULIARITIES OF FORMING FUTURE SECURITY AND DEFENSE SECTOR OFFICERS' SOCIAL AND COMMUNICATIVE COMPETENCE - Наталія БХІНДЕР; Юрій ДЕМ'ЯНЮК; Олександр КРАВЧЕНКО (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2022)
The article deals with the peculiarities of forming future security and defense sector officers' social and communicative competence. New state educational standards have been implemented. They considered competence approach to be the main methodological approach of modern higher education. Within the competence approach, the focus is on the outcome of education, which is considered not as the amount of learned information and the set of acquired skills, but as the ability to act in different situations, including problematic and non-standard ones, showing a sufficient level of competence. It is emphasized that modern graduates' knowledge, skills and abilities are characterized by a set of their key social and communicative competencies. In the article the author gives the definition of social and communicative competence and indicators of its forming. Attention is drawn to the fact that the modern army needs officers who would be true professionals in their field, have leadership qualities and be able not only to solve training and combat tasks, but also to navigate the changing social and military reality, to solve complex and multifunctional tasks while performing their professional duties. It is emphasized that an important component of officers' professionalism is their ability to interact effectively with other individuals in different conditions and situations while performing their professional activities. It is noted that in most cases, the effectiveness of such interaction is associated with military specialist's communicative skills. These skills reflect their ability to choose, establish and maintain the most appropriate communication style based on respect and personal characteristics of the interlocutor in order to achieve needed professional goals. It is emphasized that in the context of forming future security and defense sector officers' social and communicative competence, special attention should be paid to the formation of graduate's neuro-psychological stability, balance and endurance, which, in turn, guarantees a friendly and decent attitude to others. Thus, there is a need for purposeful work with cadets on their communicative skills forming, that is an important component of communicative competence in general.